937 Safe employment integration of newcomers to canada. (24th April 2018) - Kosny, Agnieszka; Yanar, Basak; Begum, Momtaz; Premji, Stephanie; Al-Khooly, Dina
Abstract : Introduction: Settlement and integration involves helping recent immigrants and refugees find work and become economically solvent. Yet many newcomers end up in 'survival jobs' that are precarious, physically demanding and expose workers to hazards. While 'welcome materials' and settlement programs help newcomers find employment, few offer guidance on employment rights, employer responsibilities and how to stay safe at work. We know very little about how newcomers prepare for employment, the types of resources needed or which groups are well-positioned to deliver these resources. Methods: Semi-structured interviews were conducted with policy makers, program developers, social service providers involved in immigrant settlement and employment preparation (n=20). Eighteen focus groups were also conducted with newcomers looking for work and those who had found their first jobs in Canada. The study examined the employment preparation and job search process; newcomer experiences in their first jobs; key training and resource needs related to safe work integration. Data were coded by two researchers and a thematic, inductive analysis was carried out. The constant comparative method was used to understand how newcomers come to understand their rights and where there are gaps in resources and training. Findings: Our findings suggest that while many programs focus on employment preparation, the delivery of OHS and rights-related resources is haphazardly and hampered by a lack of consistent funding, time constraints and a diffusion of responsibility. Newcomers reported difficulty finding work and taking jobs that were incommensurate with their experience and education. Many took on informal work without training or compensation as a means of gaining Canadian experience. Participants had poor understanding of rights and responsibilities in the workplace and many had not received comprehensive OHS training. The use of community networks, while useful in finding employment, could be a barrier to speaking up in the workplace. Language barriers were an obstacle to finding work and invoking workplace rights. Discussion: This study adds to our understanding of what can help recent immigrants and refugees successfully prepare for and stay in good quality, safe jobs. We identify optimal points in the settlement process where employment-related resources can be provided and the role social service agencies, regulatory bodies and employers should play.